The Use of Podcast in Students with Metacognitive Intervention: Foreign Language Listening Development - Hairunisa Fitriyanti; Anita Dewi Ekawati (UICELL, 2022)
Podcasts have a become everywhere and easily accessible input for dialect learning it can enhance second the formal and semantic aspects of language. It learn aims to explore several unknown effects of podcast use through a metacognitive intervention for 12th grades of senior high school. This inquire about be valid the graphic quantitative strategy. This inquire about was collected online by utilize a questionnaire via Google Form that was distributed on WhatsApp and Instagram for senior high school students in Tambun Bekasi for the 2022/2023 academic year. Listening Exploratory approach and understanding of podcast using questionnaires, study diaries, and semi-structured interviews. Respondent of this study were 30 respondents, consisting of male 17 and female 13 senior high school students in SMK Karya Bangsa Tambun. The result find that language learners enjoy several benefits when using tuning usage podcasts. Additionally, learners have shown positive evaluations toward learning to listen through metacognitive techniques, indicating that it helped them become independent listeners. The findings of this research highlights the potency of applying technology-based listening learning in EFL contexts where are the many learners do not have sufficient authentic comprehensible. Keywords: Podcast, Extensive Listening, L2 Learners, Listening Deveploment, Metacognitive Techniques